Exploring Feedback Design Perceptions and Relationships with Scores in the Online Component of an EAP-Blended Course - Anna Moni; María-Jesús Martínez-Argüelles; Enric Serradell-López (Applied Sciences)
This quantitative study investigates the perceptions of learners and faculty regarding the help provided by the feedback process, which aligns with and integrates Brooks et al.’s Matrix of Feedback for Learning in the asynchronous online component of a blended course and the relationship between student perceptions and scores. The feedback process, integrated into 12 weekly learning modules in Blackboard Learn (LMS) in alignment with Quality Matters (QM) standards for higher online education, seeks to facilitate feedback uptake and support student learning. Results from the test analysis of student (N = 135) and faculty (N = 10) surveys indicated that positive learner perceptions of feedback, corroborated by institutional course evaluations, aligned with faculty perceptions, suggesting a shared understanding of feedback’s role in learning. Interestingly, these findings suggested that feedback was perceived as beneficial independently of academic performance, potentially showing a trend of growth in students’ academic mindset, where feedback becomes a critical component of their learning experience. Additionally, this study points out that the Matrix of Feedback for Learning could be applied across different disciplinary contexts.